2004
DOI: 10.1159/000079114
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Postnatal Dexamethasone on Oxygen Toxicity in Neonatal Rats

Abstract: We investigated the effect of timing of early postnatal dexamethasone on survival of hyperoxia-exposed neonatal rats. Pups <24 h old were treated with a tapering course of dexamethasone or saline beginning either prior to exposure (day 0), or after 2, 4, or 6 days of ≧98% O2 (n = 11–14) or air (n = 8–11). Exposures were continued for 14 days. By day 14, day 0 pups had poor survival regardless of the exposure (14% in O2, 13% in air). Survival of pups treated with dexamethasone after 2, 4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In the murine model, Ohtsu et al (23) reported that higher doses of DXM (1 and 5 mg/kg/day) are required to affect survival and protect lung from hyperoxia in neonatal rats. We adopted an initial DXM dose of 0.5 mg/kg/day, because it was common initial dose used in the neonatal rat under hyperoxic conditions (24, 25). In published studies (7, 26), the postnatal HCS therapy in preterm infants, administered to prevent or treat BPD, consisted of a starting dose of 1-5 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%
“…In the murine model, Ohtsu et al (23) reported that higher doses of DXM (1 and 5 mg/kg/day) are required to affect survival and protect lung from hyperoxia in neonatal rats. We adopted an initial DXM dose of 0.5 mg/kg/day, because it was common initial dose used in the neonatal rat under hyperoxic conditions (24, 25). In published studies (7, 26), the postnatal HCS therapy in preterm infants, administered to prevent or treat BPD, consisted of a starting dose of 1-5 mg/kg/day.…”
Section: Discussionmentioning
confidence: 99%